Determinants of Occupational Fatigue and Work Accident History in Mechanical Heavy Equipment Workers at PT X site PT Z Samarinda - Lumingkewas, Meilanie Geofanni; Ramdan, Iwan Muhamad; Indira Dwika Lestari, Ida Ayu; Sultan, Muhammad; Hardianti, Dewi Novita (Jurnal Ilmiah Kesehatan Masyarakat : Media Komunikasi Komunitas Kesehatan Masyarakat, 2025)
Abstract Background: Work fatigue is critical issue that needs to be addressed properly because it can lead to various problems such as loss of efficiency at work, decreased productivity and work capacity and has the potential to cause work accidents. The factors that cause fatigue vary widely, including awkward work postures, work periods, and hot work climates. Several cases of work accidents have occurred at PT X which are suspected to be due to work fatigue. This study aims to determine the relationship between work period, work posture and work climate with work fatigue and analyze the relationship with work accident history. Method: A quantitative cross-sectional design study was conducted on 67 respondents (total sampling). The measuring instruments used consisted of questionnaires and QUESTemp 36 Heat Stress Monitor. Data were analyzed using the Spearman Rank test. Result: A total 86.6% of participants experienced mild work fatigue and 41.8% of participants had experienced work accidents. Spearman Rank test shows work periods (p = 0.022), work postures (p = 0.021) were significantly related to work fatigue. Work climate (p = 0.139) was not related to work fatigue. Work fatigue (p=0.0004) is significantly related to work accident history. Conclusion: Work periods and posture were significantly related to work fatigue. Work fatigue was related to work accidents. Control efforts are needed to reduce/overcome work fatigue experienced by workers (such as provide training on proper work posture and reducing workload) so that it does not trigger work accidents work fatigue does not occur.